The persistent constraints of new public management on sustainable co-production between non-profit professionals and service users - Caitlin McMullin (Administrative Sciences, 2023)
In this paper, I explore whether and how New Public Management (NPM) inhibits the long-term sustainability of co-production between non-profit practitioners and service users in the United Kingdom. I show how the key elements of NPM (contracts and competitive tendering, performance measurement, a pressure for non-profits to become more 'business-like', and the framing of citizens as 'customers') provide distinct barriers for non-profits to engage in co-production over the longer term, inhibiting the long-term creation of value for citizens. Through an analysis of seven case study organisations, this paper contributes to building theory about the sustainability of co-production, the factors that shape enduring co-production, and the compatibility/incompatibility of NPM tools with co-production.
Keywords: 350; co-production; New Public Management; non-profit organisations; sustainability